Seismic analysis of braced plan irregular structures using hybrid testing and numerical modelling - McCrum, Daniel P. (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2012)
The seismic behaviour of concentrically braced plan irregular structures has been investigated experimentally and numerically. An experimental programme consisting of twenty-four substructured soft-RT hybrid tests of a single-storey concentrically braced frame were undertaken. The hybrid test method combines physical dynamic testing of part of the structure with simultaneous numerical modelling of the rest of the structure. This concept is known as substructuring and allows full-scale cost effective dynamic testing. A structure can be divided into a physical and numerical substructure. The braced plan irregular structures investigated in this thesis have varying levels of torsional stiffness (lateral torsional frequency ratio) and uneven distribution of mass (static eccentricity) in plan resulting in a distribution of the centre of mass away from the centre of resistance of the structure. The consequence of this is a torsional rather than translational seismic response of the structure due to the plan irregularity.
Keywords: Civil, Structural and Environmental Engineering Ph.D.; Ph.D. Trinity College Dublin